2016
DOI: 10.1080/02640414.2016.1161204
|View full text |Cite
|
Sign up to set email alerts
|

Does installation of the backstroke start device reduce 15-m start time in swimming?

Abstract: The purpose of this study was to determine the installation of the backstroke start device reduces 15-m time. Thirteen college swimmers participated in this study. The aerial start and underwater motions were recorded with two digital video cameras. The center of mass (CM) of the swimmer, angular displacements and velocities of the shoulder, hip and knee joints were calculated. As an indicator of performance, the 5- and 15-m times were measured. The 5- and 15-m times in the backstroke start device condition we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 4 publications
2
24
0
Order By: Relevance
“…This is not consistent with a proximal-to-distal order of joint extension. It remains unclear whether proximal-to-distal joint sequencing is optimal for backstroke starts, as some studies have found it to be associated with a shorter start time [3,16], while others have not [2,4]. However, in support of our second The Effects of Plyometric Warm-up on Lower Limb Muscle Activity and Time to 10m in the Backstroke Swimming Start hypothesis, we observed that longer head entry distances were strongly correlated with shorter times to 10 m.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This is not consistent with a proximal-to-distal order of joint extension. It remains unclear whether proximal-to-distal joint sequencing is optimal for backstroke starts, as some studies have found it to be associated with a shorter start time [3,16], while others have not [2,4]. However, in support of our second The Effects of Plyometric Warm-up on Lower Limb Muscle Activity and Time to 10m in the Backstroke Swimming Start hypothesis, we observed that longer head entry distances were strongly correlated with shorter times to 10 m.…”
Section: Discussionsupporting
confidence: 62%
“…These improvements include the introduction of the backstroke ledge (also referred to as the "backstroke wedge" or "backstroke start device"; Omega OBL2, Swiss Timing, Coregmont, Switzerland) in 2014. The backstroke ledge has resulted in faster start times [2][3][4][5]; however, coaches and athletes continue to search for competitive advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a proximal to distal pattern of joint extension is generally assumed to aid in achieving a high takeoff velocity. This order of joint extension has been found related to greater performance in computer simulations of vertical jumps [7,8,10], jumps performed by participants [8,9] as well as in backstroke starts [2,11]. However, it appears that this order of joint extension is not always achieved in the backstroke start, since some studies have observed no differences in joint sequencing between starts with and without the backstroke ledge while observing improvements in start time [3,4].…”
Section: Introductionmentioning
confidence: 93%
“…In 2014, the backstroke ledge was approved by FINA (Fédération internationale de natation, or International Swimming Federation) for use in competition. The backstroke ledge alters the angle as well as the coefficient of friction between the feet and the starting surface [1], fundamentally changing backstroke start performances [2][3][4]. Accordingly, findings from previous studies where the backstroke ledge was not used may no longer be relevant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation